Establishment and characterization of a liver cell line, ALL, derived from yellowfin sea bream, Acanthopagrus latus, and its application to fish virology. Issue 1 (8th October 2021) - Li, Yong; jia, Peng; Yu, Fangzhao; Li, Wangdong; Mao, Can; Yi, Meisheng; Gu, Qunhong; Jia, Kuntong
Abstract: Yellowfin sea bream ( Acanthopagrus latus ) is an important economic fish, which is seriously threatened by various fish viruses. In this study, a cell line designated as ALL derived from the liver of yellowfin sea bream was developed and characterized. The cell line grew well in Dulbecco's modified Eagle's medium containing 10%–20% foetal bovine serum at 28°C. Amplification of the cytochrome B gene indicated that ALL cells originated from yellowfin sea bream. The modal chromosome number of ALL cells was 48. ALL cells were efficiently transfected with pEGFP‐N3 plasmids, indicating the potential application of ALL cells in exogenous gene manipulation studies. ALL cells were susceptive to three main fish viruses, including viral haemorrhagic septicaemia virus (VHSV), red‐spotted grouper nervous necrosis virus (RGNNV) and largemouth bass virus (LMBV). The replication of VHSV, RGNNV and LMBV in ALL cells was confirmed by quantitative real‐time polymerase chain reaction, virus titre and transmission electron microscopy assays. Moreover, ALL cells could respond to VHSV, RGNNV and LMBV infections, as indicated by the differential expression of antiviral genes involving in the innate immune response. In conclusion, the newly established ALL cell line will be an excellent in vitro platform for the study of the virus–yellowfin sea bream interaction.